Mechanism by Which Fiber Antigen Inhibits Multiplication of Type 5 Adenovirus - Levine, A. J. (1967)
Purified fiber antigen of type 5 adenovirus inhibited the multiplication of type 5 adenovirus by 50% when 35 μg of fiber antigen protein was added to 10(6) KB cells in suspension culture. Although the fiber antigen reduced the number of virions adsorbed per cell when a multiplicity of infection of 50,000 plaque-forming units (PFU)/cell was employed, the number of cells infected was not diminished under these conditions. If a low multiplicity of infection (1.1 PFU/cell) was used, viral adsorption was not detectably decreased. The fiber antigen did not reduce the capability of virions to liberate their viral deoxyribonucleic acid (DNA). The biosyntheses of DNA, ribonucleic acid (RNA), and protein were blocked about 20 to 25 hr after the addition of fiber antigen to cultures of uninfected or type 5 adenovirus-infected KB cells. Most of the fiber antigen protein became cell-associated between 22 and 36 hr after it was added to cells. The hexon antigen neither inhibited viral multiplication nor blocked the biosynthesis of DNA, RNA, or protein. Moreover, the hexon did not attach to KB cells. The profound effects of the fiber antigen were not due to the induction of an interferon-like substance, for actinomycin D did not reduce the ability of the fiber to inhibit multiplication of type 1 poliovirus.